Extracellular space diffusion and extrasynaptic transmission - Vargová, Lýdia; Syková, Eva (Physiological research, 2008)
The diffusion of neuroactive substances in the extracellular space (ECS) plays an important role in short- and long-distance communication between nerve cells and is the underlying mechanism of extrasynaptic (volume) transmission. The diffusion properties of the ECS are described by three parameters: 1. ECS volume fraction alpha (alpha=ECS volume/total tissue volume), 2. tortuosity lambda (lambda2=free/apparent diffusion coefficient), reflecting the presence of diffusion barriers represented by, e.g., fine neuronal and glial processes or extracellular matrix molecules and 3. nonspecific uptake k'. These diffusion parameters differ in various brain regions, and diffusion in the CNS is therefore inhomogeneous. Moreover, diffusion barriers may channel the migration of molecules in the ECS, so that diffusion is facilitated in a certain direction, i.e. diffusion in certain brain regions is anisotropic. Changes in the diffusion parameters have been found in many physiological and pathological states in which cell swelling, glial remodeling and extracellular matrix changes are key factors influencing diffusion. Changes in ECS volume, tortuosity and anisotropy significantly affect the accumulation and diffusion of neuroactive substances in the CNS and thus extrasynaptic transmission, neuron-glia communication, transmitter "spillover" and synaptic cross-talk as well as cell migration, drug delivery and treatment.
Keywords: Animals; myši transgenní; extracelulární prostor; Mice, Transgenic; Extracellular Space; Anisotropy; neuroglie; lidé; Mice; difuze; neurony; signální transdukce; myši; Signal Transduction; pohyb buněk; Central Nervous System; Neurons; anizotropie; Drug Delivery Systems; Neuroglia; krysa rodu Rattus; Diffusion; lékové transportní systémy; Cell Movement; zvířata; centrální nervový systém; Rats; Humans